Integrativ review on the training of high school human sciences teachers: an analysis of research in the last decade - Rodrigo Antonio Mattos (Tópicos Educacionais)
This article presents the results of an integrative review study on texts related to the training of high school humanities teachers published between 2011 and 2021, on the Scielo platform. It problematizes the analyses carried out on teacher education, based on the integrative review, with the objective of analyzing the scientific articles published between 2011 and 2021, which reflect on the training of teachers of Human sciences in high school. The text aims to investigate the following categories: Initial Training, Policies for teacher training based on PNE and Training and Teaching Work. The selected publications present the deficiencies in initial and continuing education, reflecting on the reading of the goals of the PNE and the deficiency in the quality of continuing education offered to teachers, and the relations between the training and valorization of the education worker.